An analysis of suppletion and word compounding in “Bangle Seller” short story - Luthfiah Nur Rokhmah; Tasya Rahmadona (LADU: Journal of Languages and Education, 2022)
Background: This paper analyzes and explains the morphological phenomena of suppletion and word compounding in a short story of Bangler. Purpose:  This study is to find out what suppletion and types of word compounding are contained in the story. Design and methods: With qualitative methods, the authors carry out this research by relying on references from books, scientific articles and documents that are still related to the research topic. Results: This study, from the analysis, revealed 7 suppletions and 4 word-compounding.